2021
DOI: 10.1177/10888683211007021
|View full text |Cite
|
Sign up to set email alerts
|

Downstream Consequences of Post-Transgression Responses: A Motive-Attribution Framework

Abstract: Victims commonly respond to experienced wrongdoing by punishing or forgiving the transgressor. While much research has looked at predictors and immediate consequences of these post-transgression responses, comparably less research has addressed the conditions under which punishment or forgiveness have positive or negative downstream consequences on the victim–transgressor relationship. Drawing from research on Social Value Orientation (SVO), we argue that both forgiveness and punishment can be rooted in either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 209 publications
(278 reference statements)
2
24
0
Order By: Relevance
“…Showing nonverbal signs of remorse appears to be sufficient to increase victims’ willingness to forgive, but only if these signs are perceived as sincere (Hornsey et al, 2020). If the victim attributes an offender’s moral change feedback to malevolent intentions (e.g., as an attempt to reduce punishment severity), such offender feedback might even have detrimental effects on forgiveness or reconciliation (Gollwitzer & Okimoto, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Showing nonverbal signs of remorse appears to be sufficient to increase victims’ willingness to forgive, but only if these signs are perceived as sincere (Hornsey et al, 2020). If the victim attributes an offender’s moral change feedback to malevolent intentions (e.g., as an attempt to reduce punishment severity), such offender feedback might even have detrimental effects on forgiveness or reconciliation (Gollwitzer & Okimoto, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…FISCHER, TWARDAWSKI, STRELAN, AND GOLLWITZER as an attempt to reduce punishment severity), such offender feedback might even have detrimental effects on forgiveness or reconciliation (Gollwitzer & Okimoto, 2021).…”
mentioning
confidence: 99%
“…It is plausible, for instance, that a poor performer responds to negative reactions that a group directs toward them, leading to downstream consequences for the group (e.g., DeShon et al, 2004). Moving toward understanding such dynamic attributions in groups, Gollwitzer and Okimoto (2021) recently provided a framework concerning dyadic interactions in forgiveness and retribution. Specifically, their model stipulates that (a) both punishment and forgiveness can be rooted in prosocial, individualistic, or competitive motives, (b) the victim can respond to transgressions according to one of these three motives, and (c) the transgressor can attribute This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Goal Attainment In Groupsmentioning
confidence: 99%
“…As noted, research has identified two very different responses that can restore a sense of moral order: punishing or forgiving the transgressor ( McCullough et al, 2010 ; Zheng et al, 2016 , 2018 ; Strelan et al, 2017 ), depending upon the alignment between motive attributions for the response and motives for the transgression ( Gollwitzer and Okimoto, 2021 ). Prior research has shown that a central (vs. peripheral) moral identity makes individuals more likely to forgive a transgressor ( Aquino and Reed, 2002 ; Aquino et al, 2007 ).…”
Section: A Social Cognitive Analysis Of Punishment and Forgivenessmentioning
confidence: 99%
“…Scholars commonly suggest two responses that may induce perceptions among members that the moral order within the organization is restored in the aftermath of a transgression—depending on whether the perceived motives for a forgiving or punitive response align with transgressor motives ( Gollwitzer and Okimoto, 2021 ). Specifically, moral transgressors may be punished for their transgression, or they may be forgiven.…”
Section: Introductionmentioning
confidence: 99%